SOME PSYCHOPATHOLODICAL PECULIARITIES AT EARLY AND LATE ONSET IN PATIENTS WITH ALZHEIMER'S DISEASE - Mariana Arnaoudova (Peytchinski Publishing, 2010)
Age-related conditions are of great medical and social importance. The most common cause of dementia is Alzheimer's disease (AD). Neuropsychiatric symptoms are an integral part of the disease and present severe problems to patients, their families, caregivers and the society at large. The aim of our work was to explore the manifestation of some psychic (non-psychotic and psychotic) and behavioral symptoms (BPSD) of hospitalized patients with early onset (EO-AD) and late onset (LO-AD) of AD with a view to compare and enrich the clinical, diagnostic and differential diagnostic possibilities. In this study significant differences in terms of BPSD between EO-AD and LO-AD patients were found. The data of EO-AD patients to be more psychotic with more behavioral problems could represent another clinical support of dividing AD not only to the age of onset.As we discuss in our paper some methodological issues, the number of examined patients in our study was comparatively small. That is why we comment some of the data as a tendency.